Digital Transformation and Innovation Leadership - Movahedpour, Nooshin (Digital Repository of Theses, 2025)
Background This study explores how innovative leadership contributes to an organization's effective digital transformation. Organizations must quickly adjust as digital technologies continue to develop in order to stay competitive. Although it is often acknowledged that leadership plays a crucial role in facilitating this process, little is known empirically about how innovative leadership in particular influences the results of digital transformation. Methods Using a mixed-methods approach, the study combined qualitative insights from open-ended survey replies with quantitative survey data from 30 firms in Germany and Dubai. Important aspects like communication, risk-taking, innovation culture, organizational preparedness, and leadership vision were the focus of the poll. The association between innovative leadership and digital transformation initiatives was investigated using statistical analysis, which included regression and correlation tests. Results The results show that innovation leadership and digital transformation are strongly positively correlated, emphasizing the need for open communication, employee empowerment, leadership vision, and agility in accomplishing digital objectives. Innovation-driven CEOs showed more openness to adopting new technology, improved teamwork, and increased agility in their organizations. The significance of leadership commitment, cultural alignment, and tackling obstacles, including aversion to change, antiquated systems, and digital skill gaps, was also underlined in the qualitative replies. Discussion and conclusion This study advances knowledge in academia and in practice by demonstrating that innovative leadership is a key driver of digital transformation as well as a supporting element. For organizational executives, consultants, and legislators looking to create more successful transformation plans, it provides practical ideas. Additionally, the study lays the groundwork for future research aimed at examining innovation-led change in many industries and regions.